Sintesis Turunan Amida N-4-O-Asetilferuloilmorfolina dari Asam Ferulat Melalui Metode Konversi Tidak Langsung - Sumarna, Sabir; Firdaus, Firdaus; Soekamto, Nunuk H. (Indonesian Journal of Chemical Research, 2016)
Synthesis of N-4-O-asetilferuloylmorpholine from ferulic acid via indirect conversion methods with acetylation, chlorination and amidation (in situ) reactions have been conducted. The acetylation was carried out using acetic anhydride reagent in pyridine solvent at room temperature for 6 hours. The chlorination was performed with thionyl chloride in benzene solvent by reflux at 75Â°C for 4 hours, proceeded by in situ amidation utilizing morpholine in the presence of triethylamine and pyridine using dichloromethane solvent at room temperature. The target molecule as white crystalline solids with m.p. of 91-92Â°C. Characterization of these compounds was committed by FTIR spectrophotometry.